Female and Male Calories Across the 19th and Early 20th Century Distributions Using Quantile Regression - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2022)
Alternative measures for material conditions are frequently used to evaluate economic welfare during development. The basal metabolic rate and calories are two alternative net nutrition measures that vary by demographics, nativity, residence, and socioeconomic status. During the 19th and early 20th centuries, males required about 20 percent more calories per day than females, and physically active laborers required more calories per day than sedentary white-collar and skilled workers. Individuals from rural Montana and the South required more calories per day than individuals from elsewhere within the US.
Keywords: Q10; Q19; N11; N51; 330; nineteenth and 20th century US gender relations; net nutrition; physical activity; nineteenth and 20th century US race relations